The immunodominant myeloperoxidase T-cell epitope induces local cell-mediated injury in antimyeloperoxidase glomerulonephritis. - Ooi, J; Chang, J; Hickey, M; Borza, D; Fugger, L; Holdsworth, SR; Kitching, A (2012)
Microscopic polyangiitis is an autoimmune small-vessel vasculitis that often manifests as focal and necrotizing glomerulonephritis and renal failure. Antineutrophil cytoplasmic Abs (ANCAs) specific for myeloperoxidase (MPO) play a role in this disease, but the role of autoreactive MPO-specific CD4(+) T cells is uncertain. By screening overlapping peptides of 20 amino acids spanning the MPO molecule, we identified an immunodominant MPO CD4(+) T-cell epitope (MPO(409-428)). Immunizing C57BL/6 mice with MPO(409-428) induced focal necrotizing glomerulonephritis similar to that seen after whole MPO immunization, when MPO was deposited in glomeruli. Transfer of an MPO(409-428)-specific CD4(+) T-cell clone to Rag1(-/-) mice induced focal necrotizing glomerulonephritis when glomerular MPO deposition was induced either by passive transfer of MPO-ANCA and LPS or by planting MPO(409-428) conjugated to a murine antiglomerular basement membrane mAb. MPO(409-428) also induced biologically active anti-MPO Abs in mice. The MPO(409-428) epitope has a minimum immunogenic core region of 11 amino acids, MPO(415-426), with several critical residues. ANCA-activated neutrophils not only induce injury but lodged the autoantigen MPO in glomeruli, allowing autoreactive anti-MPO CD4(+) cells to induce delayed type hypersensitivity-like necrotizing glomerular lesions. These studies identify an immunodominant MPO T-cell epitope and redefine how effector responses can induce injury in MPO-ANCA-associated microscopic polyangiitis.